Caring for Pediatric Patients with Acute Lymphoblastic Leukemia of Caregivers: Qualitative Study - Patcharapa Kanchanaudom, Pulsuk Siripul, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this research was to study the care of the pediatric patients with acute lymphoblastic leukemia (ALL) using a descriptive qualitative research method. Methods: Data were collected by in-depth interviews with 14 of the pediatric patients with ALL who were admitted to the pediatric ward at a tertiary hospital in the eastern region of Thailand. Data were analyzed by content analysis. Results: The care of the pediatric patients with ALL of the caregivers can be summarized into 5 important aspects as follows: 1) caring based on expectation, consisting of 2 sub-aspects: (1) decision-making on the choice of treatment and (2) inquiry sources of knowledge about care; 2) supportive care while receiving treatment, consisting of 4 sub-aspects: (1) managing complications, (2) preventing infection, (3) staying healthy and (4) receiving continuing treatment; 3) prevention the same situation care, consisting of 3 sub-aspects: (1) providing close care, (2) noticing abnormalities, and (3) changing the way of life at home; 4) fulfil the missing parts, consisting of 2 sub-aspects: (1) learning according to age and (2) brightness of age and 5) caring based on hopeless, consisting of 2 sub-aspects: (1) relieving discomfort and (2) not abandoning. Conclusion: These findings have led to a clearer understanding about the care for the pediatric with ALL of the caregivers. In addition, the data can be used to support the nursing practice in the care for the pediatric with ALL in accordance with the needs of the caregivers, the management of nursing education and further research. Keywords: Caring, Pediatric Patients, Acute Lymphoblastic Leukemia, Caregivers